HERA: A dynamic web application for visualizing community exposure to flood hazards based on storm and sea level rise scenarios. (December 2017) - Jones, Jeanne M.; Henry, Kevin; Wood, Nathan; Ng, Peter; Jamieson, Matthew
Abstract: The Hazard Exposure Reporting and Analytics (HERA) dynamic web application was created to provide a platform that makes research on community exposure to coastal-flooding hazards influenced by sea level rise accessible to planners, decision makers, and the public in a manner that is both easy to use and easily accessible. HERA allows users to (a) choose flood-hazard scenarios based on sea level rise and storm assumptions, (b) appreciate the modeling uncertainty behind a chosen hazard zone, (c) select one or several communities to examine exposure, (d) select the category of population or societal asset, and (e) choose how to look at results. The application is designed to highlight comparisons between (a) varying levels of sea level rise and coastal storms, (b) communities, (c) societal asset categories, and (d) spatial scales. Through a combination of spatial and graphical visualizations, HERA aims to help individuals and organizations to craft more informed mitigation and adaptation strategies for climate-driven coastal hazards. This paper summarizes the technologies used to maximize the user experience, in terms of interface design, visualization approaches, and data processing. Highlights: Web application for dynamic visualization of coastal storm and sea level rise impacts. Fusion of flood modeling results and socioeconomic data. Modeling uncertainty shown both spatially and in graphs of community assets. Design makes research results accessible to community practitioners.